(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
Altruism, that is, setting aside one’s own interests for the benefit of others, is a social virtue that is of great importance in society. The formation of altruism among young people plays an important role in their personal development and increasing their social responsibility. However, there are a number of obstacles to the development of altruism. This article analyzes the obstacles to the development of altruism and the research methods used to form altruism in young people.